Intervention of Development Stimulation and Nutrition Education of Complementary Feeding on The Growth and Development of Stunting Under-Free Children - Abdurrahmat, Asep Suryana; Yunianto, Andi Eka; Betaditya, Dika; Listyawardhani, Yana; Wardani, Yusrima Syamsina (Sarana Ilmu Indonesia (salnesia), 2023)
The incidence of stunting under five is also related to the low level of knowledge in providing food intake that can meet children's needs. Appropriate intervention is expected to be able to deal with stunting incidents which can be irreversible at a later stage This study aimed to determine the effect of developmental stimulation interventions and providing MP-ASI nutrition education on stunted children under five. The design of this study was experimental with pre and post design. This study used educational media MP-ASI modules and stimulation, detection, early intervention of child growth and development (SDIDTK) by first conducting developmental screening using a developmental pre-screening questionnaire (KPSP). The intervention is carried out for 1 month. The subjects in this study were 44 stunted toddlers in Condong Village using a purposive sampling method. For data that were not normally distributed, the Wilcoxon test was used to determine the significance of the effect of the intervention, and for normally distributed data, a paired t-test was used. There were significant differences in the variables of weight, height, nutritional status, height/age, and energy intake of stunting toddlers before and after the intervention (p-value<0,05). However, there were no significant differences in the variables of protein, fat intake and child development (p-value>0,05). It is necessary to carry out further research related to the duration of providing child development stimulus to stunting toddlers, so that the results of changes in child development can occur significantly.